2016
DOI: 10.14260/jemds/2016/530
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Grading of Renal Cortical Echogenicity and Raised Serum Creatinine in Patients With Chronic Kidney Disease

Abstract: BACKGROUNDChronic Kidney Disease (CKD) is a worldwide public health problem and the world's 12th commonest cause of mortality and 17th cause of morbidity. The approximate prevalence of CKD in India is 800 with an incidence of about 150-200 per million population. The most common cause of CKD is diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
8
14
0
9
Order By: Relevance
“…Similar to findings of this study, Singh A et al have reported sonographic echogenicity grade 2 (42%) as the frequent echogenicity grade, that was followed by grade 1 (35%), grade 3 (16%) and grade 4 (7%) 15 . In contrast, Siddappa et al [grade -(48%), grade 2 (35%), grade 3 (11.7%) and grade 4 (5%)] and Khadka et al [grade 1 (32%), grade 2 (31%), grade 3 (20%) and grade 4 (16%)] have reported high frequency of grade 1 and grade 4 renal cortical echogenicities 10,18 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to findings of this study, Singh A et al have reported sonographic echogenicity grade 2 (42%) as the frequent echogenicity grade, that was followed by grade 1 (35%), grade 3 (16%) and grade 4 (7%) 15 . In contrast, Siddappa et al [grade -(48%), grade 2 (35%), grade 3 (11.7%) and grade 4 (5%)] and Khadka et al [grade 1 (32%), grade 2 (31%), grade 3 (20%) and grade 4 (16%)] have reported high frequency of grade 1 and grade 4 renal cortical echogenicities 10,18 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to Khadka at al., who reported 21% small kidneys (<8cm) 10 , we found only 14% small kidneys. In agreement with Khadka et al, another study reported 35% small kidneys among CKD patients 15 . In this study, a large kidney was defined if it was >2SD of the mean renal size of the control group: >11.4 cm.…”
Section: Discussionsupporting
confidence: 89%
“…The least frequent cases were in age group >80 years (3%). Study by Singh A et al 1 showed the mean age of 54.32 year (range 19 -85 years). In their study, the most frequent age group was 51 -60 years (33%) followed by 41 -50 years (31%) and least frequent was >80 years (1%).…”
Section: Discussionmentioning
confidence: 96%
“…The grade of kidney disease is determined by cortical echogenicity with Grade 1 mild form, Grade 2 moderate form, Grade 3 severe form and Grade 4 as end-stage renal disease 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation